The tension as perturbative parameter in string theory - Gamboa, J. [UNESP] (IOP Publishing, 1990)
The author proposes an approach to string theory where the zero-order theory is the null string. An explicit form of the propagator for the null string in the momentum space is found. Considering the tension as a perturbative parameter, the perturbative series is completely summable and the propagator of the bosonic open string with tension T is found.